2012
DOI: 10.1103/physrevlett.109.128002
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Stress Profile in a Sheared Granular Column

Abstract: We present measurements of the stress as a function of vertical position in a column of granular material sheared in a cylindrical Couette device. All three components of the stress tensor on the outer cylinder were measured as a function of distance from the free surface at shear rates low enough that the material was in the dense, slow flow regime. We find that the stress profile differs fundamentally from that of fluids, from the predictions of plasticity theories, and from intuitive expectation. We argue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…In flows such as simple shear, a density gradient is set up within the shear layers . The effect of dilatancy need not, however, be confined to the shear layers—we have recently shown in our group that dilatancy causes a large‐scale secondary flow in cylindrical Couette cells, thereby explaining a stress anomaly observed earlier . It is, therefore, of interest to study the distribution of ϕ in this problem.…”
Section: Resultsmentioning
confidence: 99%
“…In flows such as simple shear, a density gradient is set up within the shear layers . The effect of dilatancy need not, however, be confined to the shear layers—we have recently shown in our group that dilatancy causes a large‐scale secondary flow in cylindrical Couette cells, thereby explaining a stress anomaly observed earlier . It is, therefore, of interest to study the distribution of ϕ in this problem.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments showed vertical stress profiles that differ qualitatively from intuitive expectations, and predictions based on isotropic plasticity. 26 He suggested that the anomalous stress profile is due to an anisotropic fabric that arises from a combined influence of gravity and shear. Farhang Radjai then presented a 2D constitutive equation deduced from DEM simulations for frictional non-cohesive disks.…”
Section: A Slow Flowmentioning
confidence: 99%
“…Our previous papers [4,5] have reported the results only for the "funneling" protocol. It is well known from prior literature that the static stress profiles for these different filling protocols will differ significantly.…”
mentioning
confidence: 99%
“…However, when the material is sheared by rotating the inner cylinder, the stress field changes dramatically. In this presentation, we shall present the findings of recent studies [4,5] of our group, wherein the stress profile for model granular materials (such as glass beads and mustard seeds) were measured at the outer cylinder using a multi-axis force sensor. The profiles are radically different from the the predictions of all plasticity theories, previous experiments, and intuitive expectation.…”
mentioning
confidence: 99%
See 1 more Smart Citation